2010
DOI: 10.1159/000320649
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Small Bowel Tumor from Descending Colon Cancer with Extensive Hematogenous or Lymphogenous Spread: Survey of the Japanese Literature

Abstract: We present the case of a 68-year-old female patient who was diagnosed with cancer of the descending colon in July 1994 and underwent partial resection of the colon (type 2, moderately to well differentiated adenocarcinoma, se, ly1, v1, n(–)). In April 1996, she was admitted to a nearby hospital for symptoms of ileus, which improved at the hospital. However, she was referred to our hospital for melena. In blood test, Hb was 8.7 g/dl, showing anemia, and carcinoembryonic antigen level was elevated to 50.7 ng/ml.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 3 publications
1
18
1
Order By: Relevance
“…Although radical surgical resection of such late colorectal metastasis is reportedly associated with a good quality of life, postoperative complication rates are considered to be high, at approaching 80%, and survival is short (ranging from 2-15 months), 2 although survival of up to 11 years has been reported. 4 This case lends support to this unfavourable picture, as our patient experienced a number of serious postoperative complications, including intraabdominal bleeding, cardiac infarction and enetrocutaneous fistula.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although radical surgical resection of such late colorectal metastasis is reportedly associated with a good quality of life, postoperative complication rates are considered to be high, at approaching 80%, and survival is short (ranging from 2-15 months), 2 although survival of up to 11 years has been reported. 4 This case lends support to this unfavourable picture, as our patient experienced a number of serious postoperative complications, including intraabdominal bleeding, cardiac infarction and enetrocutaneous fistula.…”
Section: Discussionsupporting
confidence: 64%
“…Other presentations include weight loss, ileus and obscure gastrointestinal bleeding with chronic anaemia. 4 The diagnosis is often made on a small bowel series or CT. However, neither can differentiate a primary form a metastatic small bowel cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates following resection of CRC metastasis to the small bowel are encouraging. Only 2 patients succumbed to disease progression at 1 and 26 months postoperatively (6,9,11). Furthermore, a case of disease-free survival of >11 years has also been reported (6).…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous metastasis was observed in 2 cases, while the mean time of metachronous metastasis was 7 and 36 months after surgery. The main symptoms leading to evaluation, diagnosis and surgical resection were bowel obstruction and bleeding (6). Another study reported a series of 3 cases with metachronous metastatic small bowel cancer originating from CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation